Prospects and Constraints of Madhupur National Park Management (Journal of Environmental Science and Natural Resources, 2012)
The study was conducted in Madhupur National Park (MNP), which is very well known for its characteristics as deciduous forest.  This study examined the constraints of park management, causes of deforestation and prospects of Madhupur Sal forests of Bangladesh. Data were collected from the Madhupur National Park authority and a study was done to have clear scenario of the park management and status of forest over time. It is evident from the study that due to various factors like anthropogenic disturbances, political abusement, absence of proper rules and regulations, willingless of the authority, encroachment of forest by locals/local leaders, illegal cutting of Sal trees, agro-forestry, and lack of adequate budget are main constraints for managing MNP. The study also revealed that about 1-3% of the forest is depleted each year, and about 50-80 years later, the forest will be completely vanished or scattered in somewhere. However, MNP will be a sustainable reserve forest for Sal trees and other flora and fauna, and also be a potential ecotourism spot, if it is properly managed. Findings of the study will help to identify the prospects and constraints of MNP and also in other National Parks in Bangladesh which ultimately conserve the biodiversity and help to maintain natural balance. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11570 J. Environ. Sci. & Natural Resources, 5(1): 151 - 158, 2012